XIDER: a novel X-ray detector for the next generation of high-energy synchrotron radiation sources. Issue 1 (1st December 2022) - Williams, M; Busca, P; Collonge, M; Fajardo, P; Fischer, P; Martin, T; Ritzert, M; Ruat, M; Schimansky, D
Abstract: Next-generation sources of synchrotron radiation pose significant challenges for 2D pixelated X-ray detectors, such as at the ESRF Extremely Brilliant Source (EBS), the first fourth-generation high-energy synchrotron facility. In particular, scattering and diffraction experiments require fast detectors with a high dynamic range, from single photon sensitivity to pile-up conditions under very high photon fluxes. Furthermore, in the case of high-energy applications, the high-Z sensor materials needed for efficient photon detection introduce other difficulties. Leakage current, bias- and flux-induced polarisation, and afterglow all must be carefully managed for the detector system to reach the required specifications. The XIDER project aims to fulfil the needs of the above-mentioned applications by implementing a novel incremental digital integration readout scheme. XIDER detectors seek to operate efficiently under the high-flux EBS beam of up to 100 keV photons, with a time resolution that can cope with near-continuous and pulsed beams. Simultaneously, non-constant leakage current contributions can be removed for noise-free single photon detection, resulting in a very high dynamic range. This contribution presents the recent developments of the XIDER project, including the first characterisation measurements with cadmium telluride sensors.